Implementasi Sistem Monitoring Posisi pada Overhead Crane Berbasis Internet of Things - Mukhtar; Habriansyah, Imran; Djihad, Hilal Ansyari (Politeknik Negeri Ujung Pandang, 2026)
An overhead crane is a material handling device with a bridge-like structural frame supported at both ends by wheels that move along a rail track. This equipment is generally driven by an electric motor with high torque and is widely used in industrial activities for lifting and transporting materials. However, conventional operation of overhead cranes still poses a risk of workplace accidents because operators must remain close to the crane's operating area during control. This research aims to design and implement an Internet of Things (IoT)-based position monitoring system for an overhead crane in order to improve operator safety and enable remote monitoring of crane movement. The system utilizes a NodeMCU ESP32 as a communication interface between the monitoring system and the server, while a rotary encoder is used as a sensor to detect the crane's position. The experimental results show that the developed monitoring system is capable of detecting and displaying the crane position in real time through a web-based interface. Prototype testing indicates that the system can monitor crane movement to the left and right within a position range of −500 mm to +500 mm with a reading frequency of 26 Hz and stable system performance. These results demonstrate that the proposed IoT-based monitoring system can effectively assist operators in monitoring crane movement remotely, thereby improving operational safety and efficiency in industrial environments.